REVIEW LITERATUR: PERAN GURU PENDIDIKAN JASMANI KESEHATAN DAN REKREASI DALAM PERTOLONGAN PERTAMA PADA KECELAKAAN (P3K) DI SEKOLAH - Konstantinus Tuba; Veramyta Maria Martha Flora Babang; Al Ihzan Tajudin (Jurnal Ilmu Pendidikan Jasmani Kesehatan Dan Olahraga, 2021)
This study aims to determine the role of physical education, health and recreation teachers in first aid for accidents (P3K) in schools. The method used in this research is Literature Review. The source of data in this study is using national and international journals with a total of 27 journals. Of the 27 journals, the authors found 4 journals that met the requirements by going through 3 stages of selection to be used as research results. The results of the authors reviewing 4 journals using the survey method all have positive results where all physical education, health and recreational teachers have carried out their duties well and are very satisfying. The conclusion from the results of the review that has been carried out using the Review Journal method is that the role of physical education, sports and health teachers in first aid for accidents and also in school health efforts in the school environment has been included in the very good category. So that schools are able to create and also increase comfort for students while in school, this can certainly increase student learning enthusiasm.